1991
DOI: 10.1007/bf01316750
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 alpha gene-transcription in murine keratinocytes is inhibited by HSV-1 infection

Abstract: The effect of in vitro infection with herpes simplex virus 1 (HSV-1) on the Interleukin-1 (IL-1) activity of murine keratinocytes was investigated. IL-1 alpha mRNA synthesis was measured by the Northern blot technique, and the IL-1 protein production was measured in terms of the ability of dialysed supernatants from cultures of uninfected and HSV-1 infected keratinocytes to enhance mitogen-induced murine thymocyte proliferation. IL-1 alpha mRNA-synthesis in uninfected keratinocytes was detected 24 h and 48 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In agreement with a previous report examining IL-1α mRNA expression in mouse keratinocytes infected with the HSV-1 KOS isolate 19 , we found that levels of the IL-1α mRNA were significantly down-regulated 24 hours post-infection with the HSV-1 NS isolate ( Fig. 1c ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with a previous report examining IL-1α mRNA expression in mouse keratinocytes infected with the HSV-1 KOS isolate 19 , we found that levels of the IL-1α mRNA were significantly down-regulated 24 hours post-infection with the HSV-1 NS isolate ( Fig. 1c ).…”
Section: Resultssupporting
confidence: 93%
“…Since keratinocytes express approximately 10-fold more IL-1α than IL-1β 15 , 16 , 17 and are one of the major cell types in which HSV-1 replicates, we were interested in the role of these cells in signalling danger to the host. Using direct and indirect approaches, it has previously been demonstrated that keratinocytes release IL-1α following infection with the HSV-1 isolates KOS and F 18 , 19 . TLR3 plays an important role in protecting the central nervous system from HSV-1 infections, presumably thorough detection of double stranded RNA that may be produced during the viral life-cycle 20 , 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Knowing that keratinocytes release IL-1 [Kupper et al, 1987;Enk et al, 1991], which stimulates the expression of G-CSF in different immune cells such as peripheral blood mononuclear cells [Hannen et al, 1999], bone marrow stromal cells [Kennedy and Borch, 1999], and differentiated THP-1 cells [Wang et al, 1997], here a series of experiments was carried out in order to address whether this might be the case for fibroblasts as well. As shown in Figure 5A, addition of rhIL-1b to the culture medium at concentrations above 50 and 100 pg/ml directly stimulates G-CSF expression in dermal fibroblasts (n ¼ 3).…”
Section: Keratinocyte-releasable Il-1 Is Partially Responsible For Inmentioning
confidence: 99%
“…IL‐1 α is not secreted from corneal ECs or keratinocytes following infection in vitro 15,32 . It has also been documented that HSV‐1 specifically inhibits gene transcription of IL‐1 α in keratinocytes in vitro 33 . Murine keratinocyte cell lines respond to HSV‐1 with production of IL‐10 15 which is a classic immunoregulatory cytokine.…”
Section: Discussionmentioning
confidence: 99%